GENERAL CHARACTERISTICS AND FEATURES OF PROFESSIONAL PROFILES OF LAW ENFORCEMENT OFFICERS - Oleshchenko, Veronika (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to investigate the deontological foundations and requirements for the activity of law enforcement officers, to carry out their generalization and to determine the main deontological requirements that are of basic importance for the professional profile of law enforcement agencies. The methodological basis of the research consists of general methods of thinking, functional, systemic, structural and synergistic methods. Results: it was established that the professional profile of law enforcement agencies is the result of a study by legal psychology of the psychological side of law enforcement agencies, which provides an opportunity to outline the professionally necessary mental qualities and attributes of persons engaged in the specified type of activity. Determining the importance of a professional profile in the implementation of practical legal activity, it is necessary to reflect the principles, principles and requirements for the activity of law enforcement agencies, a more detailed study and outline the characteristics of the components that make up or are embodied in law enforcement agencies. Discussion: it was established that professional profiles are psychological models of legal activity and in the process of their construction, such characteristics can be used, which can also be applied to other types of work related to the intellectual activity of a person. The complexity of professions related to law enforcement makes it necessary to create such a construction of a professional profile that would comprehensively cover its qualitative characteristics. Profession profiles of legal professions are part of the deontological characteristics of the activities of legal specialists. Each legal profession, in addition to general requirements, contains special requirements that are put forward to one or another type of activity of a lawyer, which collectively reflects the qualitative characteristics of a person applying for this type of profession. And if the issue of the professions of such legal professions as a lawyer, judge, notary is sufficiently reflected in the works of scientists and practitioners, taking into account the normative basis and international practice, then the issue of defining norms, criteria and requirements for the activities of law enforcement agencies is less reflected. This state of affairs is determined by the complex structure of the system of law enforcement agencies. Therefore, our task is to generalize the qualitative characteristics of the activities of law enforcement agencies and generalize the constituent elements of the professional profile of law enforcement agencies. Considering that the activity of law enforcement bodies, in the general sense, is a part of legal practical activity, such activity must be in accordance with the rules and principles of legal professional activity, but, at the same time, it must also have its own characteristic features. The qualities necessary in the professional activity of investigators, prosecutors, and judges are primarily related to their worldview, the consistency and direction of their views, which contribute to the development by each person of a deep understanding of the social significance of their profession and contribute to the formation of an understanding of the social significance of their profession, forms a sense of duty, justice and the desire for objectivity and honesty in activity determines the activity of a person and the desire to take part in the life of society, showing at the same time socially significant behavior and initiative.